STATE LIABILITY FOR VIOLATION OF CONSTITUTIONAL RIGHTS AGAINST INDIGENOUS PEOPLE IN FREEDOM OF RELIGION AND BELIEF - Aditya, Zaka Firma; Al-Fatih, Sholahuddin (Faculty of Law, Universitas Brawijaya, 2017)
The government is perceived as the main perpetrator on violations of freedom of religion and belief in Indonesia. As the state organizer, the government frequently issues discriminatory regulations and policies and tend to cause intolerance to minority religions and beliefs, particularly to indigenous peoples. While freedom of religion or belief is a constitutional rights that cannot be reduced and is guaranteed universally in constitution and laws, the law provides limitation that causes ambiguity in the fulfillment of the rights of religion and belief. In addition, the government mindset still adheres to the term of